2015
DOI: 10.1093/asj/sju012
|View full text |Cite
|
Sign up to set email alerts
|

Barbed Sutures and Wound Complications in Plastic Surgery: An Analysis of Outcomes

Abstract: Barbed sutures were associated with significantly higher rates of minor wound complications, specifically when the 2-layer closure technique was performed. Significantly higher rates of erythema were associated with Quill barbed sutures than with V-Loc barbed sutures. LEVEL OF EVIDENCE 4: Risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…This is important to note as pressure-induced ischemia and necrosis are major contributors to wound dehiscence [6]; however, due to the small sample size of this study and the low overall complication rate, it is not possible to determine whether wound dehiscence was prevented by the use of barbed sutures. Conversely, several retrospective reviews have reported complication rates that were significantly higher among wounds closed with barbed sutures [13, 14]. This conflict in clinical opinion indicates that additional research with a larger patient base is necessary to discern whether complications from incisions closed with barbed sutures differ significantly from standard sutures.…”
Section: Discussionmentioning
confidence: 99%
“…This is important to note as pressure-induced ischemia and necrosis are major contributors to wound dehiscence [6]; however, due to the small sample size of this study and the low overall complication rate, it is not possible to determine whether wound dehiscence was prevented by the use of barbed sutures. Conversely, several retrospective reviews have reported complication rates that were significantly higher among wounds closed with barbed sutures [13, 14]. This conflict in clinical opinion indicates that additional research with a larger patient base is necessary to discern whether complications from incisions closed with barbed sutures differ significantly from standard sutures.…”
Section: Discussionmentioning
confidence: 99%
“…There were no significant infections with implant exposure nor suture related complications due to extrusion through the skin. However, opposite findings have been published by Cortez et al 18 They reported a higher rate of minor wound complications with the use of barbed sutures, especially when these sutures were used for two-layer dermal approximation. In our experience, in order to avoid complications related to suture extrusion, it is important to place the bites far from the skin surface.…”
Section: Discussionmentioning
confidence: 72%
“…Barbed sutures evenly distribute tension and allow knot-free suture placement, decreasing the risk of dehiscence from knot breaking or slipping. 14 When placed in the papillary dermis, these sutures are associated with increased rates of minor wound complications including erythema, suture extrusion, and wound separation. 14 The ZipLine and DermaClip devices are similar in that they comprise 2 strips with adhesive coating attached by a strap bridge over the wound.…”
Section: Discussionmentioning
confidence: 99%
“… 14 When placed in the papillary dermis, these sutures are associated with increased rates of minor wound complications including erythema, suture extrusion, and wound separation. 14 The ZipLine and DermaClip devices are similar in that they comprise 2 strips with adhesive coating attached by a strap bridge over the wound. Both devices are needle free, easy to apply, and circumvent wound edge trauma.…”
Section: Discussionmentioning
confidence: 99%